From AES to Dynamic AES - Freyre, Pablo; Cuellar, Oristela; Díaz, Nelson; Alfonso, Adrián (Journal of Science and Technology on Information security, 2020)
Abstract—The cryptographic algorithm AES (Advanced Encryption Standard) works with the transformations SubBytes, ShiftRows, MixColumns and AddRoundKey, all of them fixed and selected a priori. In this paper, we will show dynamic variants of AES, where the new transformations are RandomSubBytes, RandomShiftRows, RandomMixColumns and RandomAffineTransfKey. Tóm tắt—Thuật toán mã hóa AES (Tiêu chuẩn mã hóa nâng cao) bao gồm các phép biến đổi SubBytes, ShiftRows, MixColumn và AddRoundKey. Tất cả các phép biến đổi này đều cố định và được chọn ưu tiên. Trong bài báo này, nhóm tác giả sẽ trình bày một số biến thể động của AES, trong đó các phép biến đổi mới là RandomSubBytes, RandomShiftRows, RandomMixColumns và RandomAffineTransfKey.